2019
DOI: 10.1177/1077559519892332
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Pediatric Abusive Head Trauma According to Neighborhood Social and Material Deprivation: A Population-Level Study in British Columbia, Canada

Abstract: Objectives: To explore the relationship between neighborhood social and material deprivation and the rates of abusive head trauma (AHT), and whether it differs according to sex, and following the implementation of the Period of PURPLE Crying ( PURPLE) program. Method: A cross-sectional study design was applied to data from children 0 to 24 months old with a confirmed AHT diagnosis between 2005 and 2017 in British Columbia. Dissemination area–based social and material deprivation scores were assigned to residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…These findings are consistent with prior studies that have linked deprivation with worse outcomes for a number of pediatric diseases. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Compared to traditional socio-economic measures of individual income or insurance status, a potential advantage of area-level indices such as the ADI is their ability to capture community-level effects. Additionally, area-level indices provide an assessment of the joint effect of multiple risk factors, and this composite measure may be less likely to be influenced by anomalies in a single variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with prior studies that have linked deprivation with worse outcomes for a number of pediatric diseases. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Compared to traditional socio-economic measures of individual income or insurance status, a potential advantage of area-level indices such as the ADI is their ability to capture community-level effects. Additionally, area-level indices provide an assessment of the joint effect of multiple risk factors, and this composite measure may be less likely to be influenced by anomalies in a single variable.…”
Section: Discussionmentioning
confidence: 99%
“…Various country-specific indices been used in previous studies to evaluate relationships between socioeconomic status and pediatric health outcomes, 9 with significant associations being reported in a number of studies spanning several countries. Increased neighborhood deprivation has been shown to increase a child's risk of fractures, 10,11 obesity, 12 abusive head trauma, 13 and infant mortality. 14 It has also been associated with worse outcomes for children with appendicitis, 15 asthma, [16][17][18] cystic fibrosis, 19 diabetes, 20 acute lymphoblastic leukemia, 21 and after liver and kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in knowledge on the implications of AHT have been mixed, primarily because of higher baseline knowledge about the dangers of shaking infants, leaving less room for improvement. For instance, Beaulieu et al were unable to demonstrate the effectiveness of the educational material in reducing the rates of AHT in a cross-sectional study (Beaulieu et al, 2020). Regardless of the varying population characteristics or the specific program employed, many studies have found that posteducation knowledge does improve (Barr et al, 2009;Duzinski et al, 2018;Fujiwara et al, 2012;Reese et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Confessions are always true, meaning that false confessions will never occur. It is well known, however, that both police-induced confessions and plea bargain procedures bring about false confessions (Lynøe, Juth, & Eriksson, 2019;Beaulieu, Jiang, Zheng, Rajabali, & Pike, 2019 Ad IX. The auxiliary hypothesis that all caregivers are able to shake a baby violently-independent of socioeconomic background-has been contradicted by studies in which suspects have been identified (Beaulieu, Jiang, Zheng, Rajabali, & Pike, 2019;Ghahreman, Bhasin, Chaseling, Andrews, & Lang, 2005) and is accordingly incorrect.…”
Section: Are the Mechanism Theories And The Associated Auxiliary Hypomentioning
confidence: 99%